Bulk Depolarization Fields as a Major Contributor to the Ferroelectric Reliability Performance in Lanthanum Doped Hf0.5Zr0.5O2 Capacitors - Mehmood, Furqan; Hoffmann, Michael; Lomenzo, Patrick D.; Richter, Claudia; Materano, Monica; Mikolajick, Thomas; Schroeder, Uwe (Advanced materials interfaces, 2019)
After the discovery of ferroelectricity in HfO2, many dopants have been incorporated into the material to improve the ferroelectric properties. The binary mixture of HfO2 and ZrO2, HfxZrx−1O2, showed the widest process window in terms of polarization, but other memory related aspects still need improvement. Recently, the co‐doping of La into a mixed Hf0.5Zr0.5O2, La:HZO, was reported to improve the endurance properties further but the explanation spanning both structural and electrical characteristics of La:HZO and their interaction is still missing. In this work, an extensive study of La:HZO with La content ranging from 0 to 4.3 mol% is conducted and resultant stabilization of nonpolar tetragonal phase, coercive field reduction, endurance improvement, stronger retention loss, and less imprinted hysteresis loop is reported with increasing La concentration. The model simultaneously explaining the electrical and structural properties is presented. In ferroelectric capacitor structures, the depolarization fields originating from nonferroelectric layers at the metal/ferroelectric interface are discussed extensively in previous studies but, here, for the first time, the impact of depolarization fields from nonferroelectric regions in the bulk of the ferroelectric material is reported, which is an important element to explain all the observed trends. The depolarization fields in ferroelectric materials play a vital role in defining the reliability aspects. In literature, the impact of depolarization fields originating from nonferroelectric metal/ferroelectric interface is discussed in detail but most of the time only in a qualitative way. Here, the depolarization fields originating from bulk of ferroelectric film is reported and with considering them, all of the measured results are well explained.